Identification and verification of the temozolomide resistance feature gene DACH1 in gliomas - Gu, Qiang; Li, Lang; Yao, Jiahao; Dong, Fa-yan; Gan, Yifan; Zhou, Shuhuai; Wang, Xinyu; Wang, Xue-feng (Frontiers in Oncology, 2023)
Glioma is the most common malignant brain tumor with an extremely poor prognosis. Temozolomide is the most important chemotherapy drug for patients with glioma. However, the occurrence of drug resistance greatly limits the application of temozolomide. Therefore, it is an urgent task for researchers to elucidate the mechanism of temozolomide resistance, improve temozolomide sensitivity, and prolong patient survival. Therefore, in this study, we used gene expression profiles and clinical data from the GEO, TCGA, and CGGA databases, as well as several algorithms such as differential analysis, univariate COX regression analysis, lasso regression analysis, and random forest, to build a risk model to predict the prognosis of patients treated with temozolomide, and then evaluated the performance of the model through the training and validation sets. Identification and validation of one of the model's signature genes, DACH1, by cellular experiments. With the aim of providing a model for patients treated with temozolomide to predict their prognosis and a promising target for research on temozolomide resistance,